2023
DOI: 10.24938/kutfd.1184139
|View full text |Cite
|
Sign up to set email alerts
|

The Investigation of the Effects of Vitamin D and Omega 3 on Vena Cava

Abstract: Objective: Vitamin D has a protective role in the cardiovascular system and it affects blood pressure. Omega-3 fatty acids are dietary fats gained from fish and plant oils and involve in coronary heart disease and other cardiovascular complications. The aim of the study was to investigate the effects of Vitamin D and Omega 3 on the vascular structure at the cellular level. Material and Methods: In the current study, a total of 24 rats were divided into 4 groups. Each group contained 6 animals. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…This effect is achieved through the induction of apoptosis (cell death) and G0/G1 arrest, as well as through the suppression of angiogenesis (the formation of new blood vessels) and the modulation of expression of growth factor receptors. These findings highlight the significance of vitamin D in controlling cellular processes related to cancer development [25]. VEGF of the treatment group supplemented with vitamin D at various doses, sequentially from the highest to the lowest was shown in group T3, T2, T1, and C, in the T3 group, which received a 24 iu dose of vitamin D supplementation, the VEGF expression in the lesions was found to be the lowest.…”
Section: The Association Between Varying Doses Of Vitamin D Supplemen...mentioning
confidence: 55%
See 1 more Smart Citation
“…This effect is achieved through the induction of apoptosis (cell death) and G0/G1 arrest, as well as through the suppression of angiogenesis (the formation of new blood vessels) and the modulation of expression of growth factor receptors. These findings highlight the significance of vitamin D in controlling cellular processes related to cancer development [25]. VEGF of the treatment group supplemented with vitamin D at various doses, sequentially from the highest to the lowest was shown in group T3, T2, T1, and C, in the T3 group, which received a 24 iu dose of vitamin D supplementation, the VEGF expression in the lesions was found to be the lowest.…”
Section: The Association Between Varying Doses Of Vitamin D Supplemen...mentioning
confidence: 55%
“…[15] provided evidence to support the notion that vitamin D hampers the nf-κB activation, as a result, there was a decrease in the quantity and DNA replication of abnormal endometrial cells. Furthermore, the administration of vitamin D to the mice with the endometriosis model caused a decline in the expression of VEGF-A, VEGF, and MMP-9 in the abnormal endometrial stroma, effectively suppressing the angiogenic potential associated with endometriosis [25], [16]. Delbandi et al (2016) also demonstrated the positive effects of vitamin D on endometriosis stromal cells by decreasing the rates of invasion and proliferation of the abnormal endometrial cells.…”
Section: The Association Between Varying Doses Of Vitamin D Supplemen...mentioning
confidence: 96%